Original papersA study on efficacy of 308 nm excimer light therapy in alopecia areata - Sanga, Zo Nun; Mittal, Asit (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Alopecia areata (AA) is an autoimmune condition characterized by T-cell-mediated attack on hair follicles. Objective. Evaluation of efficacy of 308 nm excimer light in the treatment of alopecia areata. Material and methods. Patches of AA were treated twice weekly, but not on 2 consecutive days, with UVB excimer 308 nm light. In all patients, half of the AA patch was irradiated and the other half was spared, covered with a black rubber shield and taken as a control. Therapy was started with an initial dose of 300 mJ/cm 2 , with an incremental dose of 100 mJ/cm 2 at every sitting until fine erythema appeared. Results. At the end of the treatment, one patient (3.33%) at the test site showed > 50% hair regrowth vs. none at the control site. After a 2-month post-treatment period, successful hair regrowth (grades 3 and 4) was seen in 12 patients at test sites and in 2 patients at control sites. The differences were statistically significant (p < 0.05). After 4 months successful hair regrowth (grades 3 and 4) was seen in 16 patients at test sites and in 5 patients at control sites. The differences were statistically significant (p 0.05). Conclusions. Excimer light has the potential to stimulate hair regrowth in patches of alopecia areata.